0767 Long-term Safety Of Sodium Oxybate In Pediatric Narcolepsy With Cataplexy: Open-label Continuation Post 1-year of Treatment. (12th April 2019) - Strunc, Michael J; Mignot, Emmanuel; Wang, Grace; Black, Jed; Chakravarthy, Divya; Parvataneni, Rupa; Plazzi, Giuseppe
Abstract: Introduction: In a placebo-controlled, randomized withdrawal study with subsequent open-label investigation for up to 1 year, sodium oxybate (SXB) demonstrated efficacy and safety in the treatment of pediatric narcolepsy with cataplexy. In a further continuation period for up to 2 years, safety of SXB and effects on growth were assessed. Methods: Participants who completed Part 1 (up to 52 weeks on study) could transition or re-enroll into the open-label continuation (Part 2) for up to an additional 2 years. Part 2 evaluations included body mass index (BMI), weight, height, treatment-emergent adverse events (TEAEs), and vital signs. Age- and sex-based percentiles for height, weight, and BMI at each assessment were determined using standardized growth charts (CDC, 2000). Results: As of 30 April 2018, of the 44 participants in Part 2, 1 completed and 4 discontinued (3 withdrew consent, 1 lost to follow-up). Mean (SD) age at first SXB dose in Part 2 was 13.1 (2.2) years; 29.5% were 7-11 years, 70.5% 12-17 years; 68.2% male; and 65.9% white. In Part 1, mean baseline BMI was elevated relative to age-matched population means. In Part 1, there was slight initial decrease from baseline in median BMI and weight percentile values, which stabilized, and remained within normal range in Part 2 (median change from baseline to Part 2 month 3: BMI percentile -2.8%; weight percentile -2.4%). There was increase in absolute height and slight decrease in height percentile (median change from baseline to Part 2 month 3: height 9.0 cm, height percentile -2.0). In Part 2, TEAEs were reported in 18/44 (40.9%) participants; most frequent TEAEs were respiratory tract infection (6.8%), constipation (4.5%), diarrhea (4.5%), gamma-glutamyltransferase increased (4.5%), headache (4.5%), weight increased (4.5%). As of 30 April 2018, for Part 2, there were no serious AEs reported and no discontinuations due to TEAEs. Vital signs remained within normal range throughout the study. Conclusion: Growth parameters remained stable overall, and no new safety findings were identified during the ≤2-year open-label continuation period (Part 2). Support (If Any): Jazz Pharmaceuticals